The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Day 3 Wed, April 26, 2017 2017
DOI: 10.2118/188016-ms
|View full text |Cite
|
Sign up to set email alerts
|

New Technique to Determine the Total Organic Carbon Based on Well Logs Using Artificial Neural Network (White Box)

Abstract: Total organic carbon (TOC) is the amount of carbon present in an organic compound and is often used as an essential factor for unconventional shale resources evaluation. The previous models for TOC determination were either based on density log data only and considered the presence of organic matter is proportional to the bulk density, or based on resistivity log, sonic or density logs as well as the formation level of maturity (LOM), where these models assumed a linear relation between resistivity and porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Machine learning techniques are used in several scientific and engineering fields since the early 1990s to solve complicated non-linear problems. Petroleum engineers and petroleum geologists use different machine learning techniques to solve problems related to petroleum industry, such as the characterization of the heterogeneous hydrocarbon reservoirs [33,34], evaluation of the reserve of unconventional reservoirs [35][36][37][38], estimation of the rock mechanical parameters, such as the static Poisson's ratio in carbonate reservoirs [39] and the static Young's modulus for sandstone reservoirs [24,40], evaluation of the integrity of wellbore casing [41,42], optimization of drilling hydraulics [43], evaluation of pore pressure and fracture pressure [44,45], hydrocarbon recovery factor estimation [46,47], determination of the alteration in the drilling fluids rheology in real-time [48,49], optimization of rate of penetration [50,51], prediction of the formation tops [52], and others.…”
Section: Applications Of Machine Learning In Petroleum Engineeringmentioning
confidence: 99%
“…Machine learning techniques are used in several scientific and engineering fields since the early 1990s to solve complicated non-linear problems. Petroleum engineers and petroleum geologists use different machine learning techniques to solve problems related to petroleum industry, such as the characterization of the heterogeneous hydrocarbon reservoirs [33,34], evaluation of the reserve of unconventional reservoirs [35][36][37][38], estimation of the rock mechanical parameters, such as the static Poisson's ratio in carbonate reservoirs [39] and the static Young's modulus for sandstone reservoirs [24,40], evaluation of the integrity of wellbore casing [41,42], optimization of drilling hydraulics [43], evaluation of pore pressure and fracture pressure [44,45], hydrocarbon recovery factor estimation [46,47], determination of the alteration in the drilling fluids rheology in real-time [48,49], optimization of rate of penetration [50,51], prediction of the formation tops [52], and others.…”
Section: Applications Of Machine Learning In Petroleum Engineeringmentioning
confidence: 99%
“…AI techniques are used extensively in applications related to different engineering and scientific research areas [15][16][17][18][19][20], including in the petroleum industry where they can solve complicated problems such as prediction of drill bit wear from drilling parameters [21], real-time predictions of alterations in drilling fluid rheology [22,23], lithology identification [24], prediction of total organic carbon for the evaluation of unconventional resources [25][26][27][28][29], estimation of the oil recovery factor [30,31], estimation of pore and fracture pressures [32,33], evaluation of the static Young's modulus [34][35][36], estimation of the reservoir porosity [37], evaluation of the bubble point pressure [38], and the prediction of formation tops [39].…”
Section: Application Of Artificial Intelligence For Rate Of Penetratimentioning
confidence: 99%
“…Applying any of the previously discussed correlations to evaluate TOC in formations different than the one developed leads to inaccurate predictions. Recently, Mahmoud et al [18,19] suggested an artificial neural network (ANN)-based correlation for TOC estimation in Barnett formation using conventional well logs. Later on, Elkatatny [20] applied the self-adaptive differential evolution algorithm to optimize Mahmoud et al's [18,19] ANN model and he was able to improve the model predictability.…”
Section: His Correlation In Equationmentioning
confidence: 99%
“…Since the early 1990s, AI techniques had been extensively applied in many scientific and engineering fields, including in the petroleum industry. Nowadays, AI has been used by petroleum engineers and geologists to solve problems related to unconventional hydrocarbon resources evaluation [18][19][20], reservoir characterization [21,22], bubble point pressure evaluation [23], prediction of real-time change in the rheological parameters of the drilling fluids [24,25], optimization of rate of penetration [26], estimation of rock mechanical parameters [27,28], prediction of pore pressure and fracture pressure [29,30], evaluation of the wellbore casing integrity [31,32], hydrocarbon recovery factor estimation [33,34] optimization of the drilling hydraulics [35], and others. AI techniques have also been applied successfully in other fields like social media [36,37].…”
Section: Different Applications Of Artificial Intelligence Techniquesmentioning
confidence: 99%
See 1 more Smart Citation